Feature address to the OECS Third Biennial Meeting on Fisheries Management and Development of Ministers Responsible for Fisheries, July 23rd 1992, St. Kitts and Nevis - Yankey, J. Bernard ([s.n.] [s.l.], 1992)
Suggests there should be continuous training of fishermen to improve their skills at fishing and there by to increase earnings. Proposes the establishment of an OECS Fisheries investment company which would develop an investment prospectus covering the various alternative fishing enterprises that could be launched on a commercial basis, as a viable business.